INTERROGATING PARENTAL PARTICIPATION IN THE EDUCATION AND GENERAL DEVELOPMENT OF THEIR DEAF CHILDREN IN ZAMBIA (African Disability Rights Yearbook, 2021)
Parents have a critical role to play in the education of their children. Their participation is likely to facilitate positive academic achievement and optimal development. In any case, parents’ participation is a gateway to realising full inclusion of Deaf children in schools. This study interrogated the participation of parents and guardians in the education and general development of their Deaf children. A survey of 85 parents and guardians was conducted in seven districts of six provinces in Zambia. A mixed-method approach was employed. Closed and open ended questionnaires were used to collect both quantitative and qualitative data. The Statistical Package for Social Sciences (SPSS) version 16 was used to analyse quantitative data. From the quantitative analysis, frequencies, percentages and correlations between variables such as sex and data on the relationship and the desire to learn Sign Language were obtained. A Chi square test of independence helped to establish possible relationships. Verbatim excerpts from qualitative data were used to support quantitative data. The results showed that parents and guardians of Deaf children faced challenges in communicating with their children. Further, parents’ participation in the education of Deaf children was limited by difficulties in communication and lack of support from experts. No significant differences were observed between male and female parents and guardians in relation to knowing Sign Language as the main challenge they faced. The study concluded that the realisation of full inclusive education should start from home. Based on the results, it was recommended that the Ministry of General Education and other stakeholders should provide outreach services which include lessons in Sign Language for parents to enhance their participation in the education and general development of Deaf children.
Keywords: parents and guardians; education and development of deaf children; Zambia; challenges in communicating; Sign Language